Complete chloroplast genome sequence of Acer nikoense (Sapindaceae). Issue 3 (2nd July 2020) - Fu, Qidi; Yu, Xuedan; Xia, Xinhe; Zheng, Yongqi; Zhang, Chuanhong
Abstract: Acer nikoense (Sapindaceae: Acer) is a deciduous tree, belonging to the Ser. Grisea of Sect. Trifoliata . Its complete genome sequence was obtained using genome Illumina pair-end sequencing data. It had a typical quadripartite structure with 155, 952 bp in length, consisting of a large single-copy region (85, 720 bp) and a small single-copy region (18, 072 bp), as well as a pair of inverted repeats (26, 080 bp). The total GC content was 37.9%. A total of 113 unique genes were annotated, including 30 tRNAs, 4 rRNAs, and 79 protein-coding genes. The phylogenetic analysis indicated that A. nikoense and A. triflorum were the most closely related.